ON AN EXPERIMENTAL SEED COLLECTION AND FIELD CULTURE OF KING PRAWN, PENAEUS LATISULCATUS - Kathirvel, M; Selvaraj, V (Indian Journal of Fisheries, 2011)
Early juveniles of the King prawn, Penaeiis latisulcatus Kishinouye, were caught from the sandy barmouth area of Kovalam backwater, near Madras, during May-July 1986. These were successfully cultivated in an earthern pond at the Muttukadu Maricuiture Centre of the Institute for a period of 80 days supplementing backwater clam (Meretrix casta) for feed. Over this time the females were found grown up and with developing ovary. The size-frequency analysis of the juveniles obtained from the wild and those reared showed a grovrth of 29-30 mm per month. The hatchery-raised postlarvae of the species were reared on a diet of zooplankton (copepods, rotifers and freshwater cladocerans) and moUuscan meat (boiled flesh of clam and mussel). Those reared on copepod diet exhibited faster growth and those reared on a combination of zooplankton and molluscan meat exhibited higher survival